ANALISIS KESALAHAN MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL PADA PEMBELAJARAN DARING SISWA SMP KELAS VIII - Nuraidha, Resti (IKIP Siliwangi, 2023)
Goal of this study was to examine the mistakes made by SMP Plus Al-Irfan students as they attempted to solve a system of two linear equations using online instruction. Research is being conducted using the descriptive qualitative technique. The research involved a total of 28 SMP Plus Al-Irfan class VIII students. The test instrument consists of six description-style questions. The indicators are: (1) Determining the distinction between PLDV and SPLDV; (2) Create a mathematical model and solving SPLDV use elimination methode; (3) Create a mathematical model, and solving SPLDV and use the substitution method; (4) Create a mathematical model, and solving SPLDV use the combined method; (5) Identifying special SPLDV and its solutions; and (6) Create a mathematical mode and solving SPLDV use the graphical method. According to the study's findings, junior high school students made the most mistakes in identifying the SPLDV graphical method's completion indication, with an error rate of 85.5%. According to the primary factor analysis's findings, students make mistakes, particularly when trying to convert story questions into mathematical models and create SPLDV graphs.